2016
DOI: 10.1371/journal.pone.0164258
|View full text |Cite
|
Sign up to set email alerts
|

The Architectural Chromatin Factor High Mobility Group A1 Enhances DNA Ligase IV Activity Influencing DNA Repair

Abstract: The HMGA1 architectural transcription factor is an oncogene overexpressed in the vast majority of human cancers. HMGA1 is a highly connected node in the nuclear molecular network and the key aspect of HMGA1 involvement in cancer development is that HMGA1 simultaneously confers cells multiple oncogenic hits, ranging from global chromatin structural and gene expression modifications up to the direct functional alterations of key cellular proteins. Interestingly, HMGA1 also modulates DNA damage repair pathways. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…To this end we silenced the expression of HMGA1 with siA1_3 [19] in the mesenchymal-like TNBC MDA-MB-231 and MDA-MB-157 cell lines, which express high level of this protein. We performed also the reverse experiment by using a previously established cell line [35] where HMGA1 is overexpressed in the Luminal A breast cancer cell line MCF7, where endogenous HMGA1 is barely detectable and cells exhibit an epithelial phenotype. In all these three cell lines, HMGA1 expression has been associated to the acquisition of a mesenchymal phenotype [19,36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end we silenced the expression of HMGA1 with siA1_3 [19] in the mesenchymal-like TNBC MDA-MB-231 and MDA-MB-157 cell lines, which express high level of this protein. We performed also the reverse experiment by using a previously established cell line [35] where HMGA1 is overexpressed in the Luminal A breast cancer cell line MCF7, where endogenous HMGA1 is barely detectable and cells exhibit an epithelial phenotype. In all these three cell lines, HMGA1 expression has been associated to the acquisition of a mesenchymal phenotype [19,36].…”
Section: Resultsmentioning
confidence: 99%
“…Cell lines were kindly provided by the laboratory of prof. G. Del Sal (Laboratorio Nazionale CIB (LNCIB) Area Science Park, Trieste, Italy). Cells were cultured as previously described [20,35]: MDA-MB-231 and MDA-MB-157 cells were grown in DMEM supplemented with 2 mM L-glutamine, 10% tetracycline free fetal bovine serum (Tet-free FBS, Euroclone, Pero, Italy), penicillin (100 U/mL, Euroclone), streptomycin (100 μg/mL, Euroclone). MCF7 cells were grown in Dulbecco’s MEM Nutrient Mix F12 (1:1) with 25 mM HEPES (DME/F12-HEPES, Euroclone) supplemented with 2 mM L-glutamine, 10% tetracycline free fetal bovine serum (Tet-free FBS, Euroclone), penicillin (100 U/mL, Euroclone), streptomycin (100 μg/mL, Euroclone), and 1X MEM non-essential amino acids (Sigma Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-mobility group AT-hook1 (HMGA1, formerly HMG-I/Y), an architectural transcription factor, can bind to AT-rich regions in the minor groove of DNA 4 . It participates in a myriad of fundamental cellular processes, including cell cycle progression 5 10 , embryologic development 11 , 12 , neoplastic transformation 13 18 , differentiation 19 , apoptosis 20 23 , cellular metabolism 24 , 25 , and DNA repair 26 29 . Numerous pieces of evidence have demonstrated that HMGA1 is widely overexpressed in a variety of human carcinomas, such as pancreatic cancer 30 , colon cancer 18 , 31 , 32 , breast cancer 33 – 36 , and cervical cancer 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Another property of these proteins has emerged recently: their DNA protective function in cancer cells or in response to genotoxic treatment. Very recent work places HMGA1 in a complex with DNA-PK to enhance ligase IV activity (Pellarin et al, 2016). In cells overexpressing HMGA2, the presence of DNA-PKcs at these DSB sites is prolonged and alters the binding of KU70/ 80.…”
mentioning
confidence: 99%